Randomized, open-label, two-way crossover bioequivalence study of Novirax (Drug International Ltd, Bangladesh) compared with Zovirax (Glaxo Wellcome, UK) – two brands of Acyclovir – in healthy male volunteers - Sarker, Uttam Kumar; Hossain, Mezbah; Islam, Md. Atikul; Shamsuzzoha, Md.; Najim Uddin, Md.; Misbahuddin, Mir; Mollah, Md. Elias; Islam, Md. Rabiul (Asian Journal of Pharmaceutical Research and Development, 2021)
Objectives: A crossover-randomized bioequivalence study of two oral formulations of acyclovir 200 mg tablet was accomplished with 16 adults and physically fit male volunteers from Bangladesh. NOVIRAX™ (Drug International Ltd, Bangladesh) was the test variant whereas ZOVIRAX™ (GlaxoWellcome) was the reference one. Methods: After a night fasting each volunteer was subjected to take a single dosage of tablet with 150 mL of water. After a week for complete washing out, a second dosage was applied. After that, blood samples were collected at a serial interval for a 24 hours period to observe the plasma concentration by HPLC technique. Several pharmacokinetic parameters like Cmax, Tmax, AUC0→24h, t1/2, and Kel were estimated. Results: The mean (± SD) AUC0→24h for acyclovir of test variant NOVIRAXTM for 16 participants was 1057.5 ± 358.9 ng/hr/mL whereas it was 1134.9 ± 467.2 ng/hr/mL for acyclovir of ZOVIRAXTM. The relative bioavailability (NOVIRAXTM/ZOVIRAXTM ratio) was 93.2%. The Cmax, tmax, half-life of elimination (t1/2) and the rate of elimination (Kel) of acyclovir of test drug were 207.0 ± 86.9 ng/mL, 2.4 ± 0.4 hours, 3.2 ± 1.8 hour and 0.0898 respectively. The Cmax, tmax, half-life of elimination (t1/2) and the rate of elimination (Kel) of acyclovir of reference drug were 230.7 ± 107.2 ng/mL, 2.0 ± 0.9 hours, 2.8 ± 1.2 hour and 0.0921 respectively. Conclusion: Depend on these statistical speculations; it was culminated that a NOVIRAX tablet is bioequivalent to a ZOVIRAX tablet.